Study of the Coexistence of Helicobacter pylori and Candida in the Saliva of Patients with Dyspepsia - Karthick B, Prem; Rao, Umadevi K; Joshua, Elizabeth; K, Ranganathan (UI Scholars Hub, 2019)
Background: Helicobacter pylori (H. pylori), a gram negative micro-aerophilic bacterium is known to cause gastritis, peptic ulcer disease and gastric adenocarcinoma. Extra-gastric reservoir of this bacteria can cause recurrent infection in treated subjects. Oral cavity is considered to be an important extragastric reservoir due to the favourable milieu in sub gingival areas and the symbiotic association H. pylori shares with Candida, a common commensal in the oral cavity. Objective: To evaluate the presence of H. pylori and Candida in the saliva of patients with chronic gastritis. Methods: The study compromised of subjects with H. pylori positive gastritis (Group I: n=30), subjects with H. pylori negative gastritis (Group II: n=30) and normal controls without gastritis (Group III: n=10). Unstimulated saliva samples (Whole mouth fluid) was collected and subjected to real time PCR analysis for the detection of Urease A gene of H. pylori. Sabouraud’s Dextrose Agar was used to detect the presence of Candida species. Results: Seven subjects (23.3%) from Group I and four subjects (13.3%) from Group II were positive for oral Helicobacter pylori. Fourteen subjects (46.6%) from Group I and Eight subjects (26.6%) from Group II showed the presence of oral Candida. Four subjects (13.3%) from Group I had both oral Helicobacter pylori and oral Candida. Conclusion: H. pylori and Candida in the oral cavity could potentially influence H. pylori recolonization of the gastric mucosa leading to recurrent gastritis.